RETRACTED: Carbon impact on surface morphology and electrical properties of Cu-TiC thin film - Avishek Roy; Shilabati Hembram; Manojit Ghosh; Abhijit Majumdar (Materials Research Express)
In recent years, synthesis of TiC reinforced Cu matrix composites are comprehensively utilized for industrial applications. Synthesis of Cu-TiC as a thin film can also be an intriguing challenge for such applications. In this work, Cu-TiC thin film was deposited by DC magnetron co-sputtering method and examined to investigate the role of C content on the micro-structure, electrical conductivity and surface morphology by using XRD, UV–vis spectroscopy, I-V characteristics, AFM, SEM and EDX analysis. The wt% of C was varied from 14 to 67% while depositing the Cu-TiC films. All the films have resulted to be polycrystalline with Cu and TiC phases. The optical band-gap has decreased from 2.59 to 1.93 eV and the refractive index got enhanced from 2.92 to 3.38 with increase in wt% of C. The ideality factor, electrical resistance, surface roughness across the films has also decreased as wt% of C was increased in Cu-TiC films.